STRATEGI PEMASARAN PADA PRODUK DIMSUM MENTAI TERHADAP PENINGKATAN PENDAPATAN DENGAN MEMANFAATKAN MEDIA SOSIAL DI ERA DIGITAL - Dara Nursyifa Sofian; Muthi’ Dwika Ningrum; Putri Diana Sari; Sukma Ali Winata; Siti Maimunah (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2024)
This study is driven by the various sales trends observed through the utilization of social media, particularly in today's digital age. Marketing strategies via social media play a crucial role for entrepreneurs, especially in the dimsum industry where the wide array of dimsum varieties serves as a unique attraction for consumers. The effectiveness of social media in this context cannot be overstated. The research employs a descriptive qualitative approach, involving analysis, data collection, and subsequent application. This method does not involve statistical procedures, but rather aims to address specific issues by providing a detailed description of the research subject based on field observations. The investigation into the mentai dim sum business underscores the significance of social media as a key strategy for revenue growth. The impact of social media on revenue generation is substantial, as it facilitates closer consumer engagement and enhances product visibility.